Ambient Temperature Ligation of Diene Functional Polymer and Peptide Strands onto Cellulose via Photochemical and Thermal Protocols. Issue 12 (6th April 2014) - Tischer, Thomas; Claus, Tanja K.; Oehlenschlaeger, Kim K.; Trouillet, Vanessa; Bruns, Michael; Welle, Alexander; Linkert, Katharina; Goldmann, Anja S.; Börner, Hans G.; Barner‐Kowollik, Christopher
<x xml:space="preserve">Abstract</x> In the present contribution, two novel ambient temperature avenues are introduced to functionalize solid cellulose substrates in a modular fashion with synthetic polymer strands (poly(trifluoro ethyl methacrylate), PTFEMA, Mn = 4400 g mol−1, Đ = 1.18) and an Arg‐Gly‐Asp (RGD) containing peptide sequence. Both protocols rely on a hetero Diels–Alder reaction between an activated thiocarbonyl functionality and a diene species. In the first—thermally activated—protocol, the cellulose features surface‐expressed thiocarbonylthio compounds, which readily react with diene terminal macromolecules at ambient temperature. In the second protocol, the reactive ene species are photochemically generated based on a phenacyl sulfide‐decorated cellulose surface, which upon irradiation expresses highly reactive thioaldehyde species. The generated functional hybrid surfaces are characterized in‐depth via ToF‐SIMS and XPS analysis, revealing the successful covalent attachment of the grafted materials, including the spatially resolved patterning of both synthetic polymers and peptide strands using the photochemical protocol. The study thus provides a versatile platform technology for solid cellulose substrate modification via efficient thermal and photochemical ligation strategies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>